Electronic Supply Chain Management Role in Marxism Economy in Russia - Vasilievna, Lapteva Elena; Vladislavovich, Ostroumov Vladimir; Venediktovna, Gorohovairina (International Journal of Supply Chain Management, 2019)
This article investigates the electronic supply chain capitalism as a model for understanding both the continent-crossing scale and the constitutive diversity of contemporary globalcapitalism based on the Marxism Economy in Russia. The purpose of this work is to give a brief analysis of the development of Marx's doctrine in Western and Russian economic and social science thought, from the late XIX to the early XX centuries. The author presents a brief overview of how the attitude towards Marx and his main work ‘Capital’ changed from the era of his contemporaries to the present time in several main directions. The article also draws attention to the critical attitude of Marx towards Russia.The author emphasizes that Marxism (the conceptual legacy of Marx) became the basis for many doctrines around the world in the twentieth century. Karl Marx became popular not only as a great economist, but also as a sociologist, a creator of the doctrine of the downfall of capitalism and coming revolution, and a forecaster-futurist. The author in his article refers to various sources - from monographs of famous scientists to interviews published in press and online sources by representatives of various social strata. The author comes to the conclusion that at the present moment interest in Marx and his teaching persists in three main planes: among academics, in the left-wing radical environment and at the level of common interest, the latter, in crisis years, gaining momentum. The author also emphasizes that interest in Marx and his teaching was manifested regionally in different planes; Marx as an economist was more popular in the West and as a futurist and revolutionary thinker in the East. The continued constant interest in Marx and his works throughout the world testifies by considering the electronic supply chain management which is teaching of Marx still remains relevant.